2020
DOI: 10.1371/journal.pone.0228914
|View full text |Cite
|
Sign up to set email alerts
|

Why we publish where we do: Faculty publishing values and their relationship to review, promotion and tenure expectations

Abstract: Using an online survey of academics at 55 randomly selected institutions across the US and Canada, we explore priorities for publishing decisions and their perceived importance within review, promotion, and tenure (RPT). We find that respondents most value journal readership, while they believe their peers most value prestige and related metrics such as impact factor when submitting their work for publication. Respondents indicated that total number of publications, number of publications per year, and journal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 26 publications
4
109
0
2
Order By: Relevance
“…The 2020 PLoS Biology article updated the previous citation database to include citations up to the end of 2019. In addition, 1 Based on a search of PUBMED and review of actual published articles 2 Rank among the top 100,000 most cited scientists in all scientific disciplines 3 NSC no self-citations counted 4 WSC with self-citations counted it included the names of scientists if they were among the topcited 2% within their scientific discipline. The number of forensic practitioners represented now increased from 30 to 215 and the total number of scientists within this discipline was 10,158.…”
Section: Expanded List Of Highly Cited Scientistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2020 PLoS Biology article updated the previous citation database to include citations up to the end of 2019. In addition, 1 Based on a search of PUBMED and review of actual published articles 2 Rank among the top 100,000 most cited scientists in all scientific disciplines 3 NSC no self-citations counted 4 WSC with self-citations counted it included the names of scientists if they were among the topcited 2% within their scientific discipline. The number of forensic practitioners represented now increased from 30 to 215 and the total number of scientists within this discipline was 10,158.…”
Section: Expanded List Of Highly Cited Scientistsmentioning
confidence: 99%
“…This is particularly beneficial in university, such as when people apply for promotion or tenure and when research funding decisions are made. A strong publication track record is important and is always one of the key consideration when people apply for research grants and scholarships [3][4][5]. However, the raw number of publications can be misleading when judging the merits of a person's work, without also considering the pattern of authorship and impact factors of the journals [6].…”
Section: Introductionmentioning
confidence: 99%
“…This could point to distinct regional and disciplinary academic cultures and, indeed, a recent study found that North American SSH researchers are generally more skeptical of the benefits of OA (Bongiovani, Gómez, & Miguel, 2012;Dalton, Tenopir, & Björk, 2020). Similarly, academic career progression in North America rarely provides incentives for active involvement in OA journals (e.g., through publications or editorial roles; see Alperin et al, 2019;Niles, Schimanski, McKiernan, & Alperin, 2020). Signalizing which contributions are valued could have an impact far beyond authors' publishing decisions and also affect perceptions of what is worth preserving.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one of the greatest ironies of the scarcity-fueled system of hypercompetition in which scholars in HSS now find themselves is the apparent mismatch between scholars' own values and those they believe the academy to hold. A recent survey by the ScholCommLab (Niles et al, 2020) that asked faculty members why they publish where they do elucidates this phenomenon. "Put plainly", the authors write, "our work suggests that faculty are guided by a perception that their peers are more driven by journal prestige, journal metrics (i.e., JIF [journal impact factor] and journal citations), and money (i.e., merit pay) than they are, while they themselves value readership and open access of a journal more".…”
Section: Perverse Incentivesmentioning
confidence: 99%